Case Report: Surgical Reconstruction of a Massive Thoracic Wall Defect After the Resection of an Undifferentiated Radiation-Induced Sarcoma of the Breast - Rastrelli, Marco; Di Prata, Claudia; Marconato, Roberto; Del Fiore, Paolo; Granziera, Elisa; Brunello, Antonella; Vindigni, Vincenzo; Zuin, Andrea; Sbaraglia, Marta; Tropea, Saveria; Mocellin, Simone (Frontiers in Surgery, 2021)
A 54-year-old lady was referred to our institute because of a massive thoracic neoplasm arising from the thoracic wall which infiltrated and dislocated the left breast. Twenty years before, the patient had undergone a quadrantectomy with axillary dissection for an infiltrating ductal carcinoma of the left breast, followed by adjuvant radiotherapy and chemotherapy. A true-cut biopsy of the mass showed a low differentiated malignant neoplasm with spindle-shaped cells. The patient underwent a total-body CT scan which showed a 16 × 15 × 10 cm largely necrotic mass with irregular and undefined margins, with little homolateral round-shaped cervical and mesenteric lymph nodes but no distant metastases. After a multidisciplinary discussion, we proposed surgery as the first therapeutic option. The planned treatment was a wide excision of the mass with the underlying ribs (II-VI) followed by the reconstruction of the thoracic wall using titanium bars covered by the acellular porcine dermis, latissimus dorsi flap, and finally, skin grafts from the thighs.